2018
DOI: 10.3389/fsufs.2018.00054
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Release of Phosphorus and Potassium From Lignocellulosic- and Manure-Based Biochars for Fertilizer Reuse

Abstract: Biochars pyrolyzed from plant residues and animal manure feedstocks may contain disproportionate amounts of phosphorus (P) and potassium (K). Unequal nutrient characteristics can impact the biochars ability to properly supply as well as improve soil P and K fertility levels. A soil incubation study was performed to test the hypotheses that biochar produced from poultry litter will release more water soluble dissolved P (DP) and K (DK) concentrations and would also increase soil plant available P and K concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…Previous studies suggest however, that for biochar to make a viable contribution to soil N, P, and K nutrient pools, the nutrients need to be released into the soil solution in concentrations within ranges suitable for plant uptake and increased crop production [20]. Moreover, the rates of nutrient release in different biochar will depend on the nutrient pool in the biochar and the soil conditions [51].…”
Section: Recovery Of Nutrients Via Biochar Sorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest however, that for biochar to make a viable contribution to soil N, P, and K nutrient pools, the nutrients need to be released into the soil solution in concentrations within ranges suitable for plant uptake and increased crop production [20]. Moreover, the rates of nutrient release in different biochar will depend on the nutrient pool in the biochar and the soil conditions [51].…”
Section: Recovery Of Nutrients Via Biochar Sorptionmentioning
confidence: 99%
“…Indeed, several studies have demonstrated that biochar can adsorb nitrogen (as NH 4 + -N, NO 3 − -N, and Urea), phosphorus (as orthophosphate), potassium, and organic matter from different aqueous solutions such as landfill leachates, anaerobic digestates, urine, and livestock wastewater [15][16][17][18]. As a soil amendment, biochar has been reported to offer several benefits, which include increased soil texture, soil carbon, nutrient retention, and cation exchange capacity, beside support to microbial diversity that increases mineralization and availability of nutrients in amended soils [19][20][21]. In a recent study, Fidel et al [22] evaluated the potential reduction of greenhouse gases (N 2 O and CO 2 ) emissions from biochar-amended soils based on laboratory soil incubations experiments and field scale studies under continuous cropping with four crop systems namely; no-till continuous corn, switch grass, forb mix, low-diversity and high-diversity grass mix.…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of P present in biochar is source dependent; biochars produced from nutrient-rich feedstocks, such as manure and crop residues, generally have higher P values than those from lignocellulosic feedstocks, and therefore are best suited to be used as soil P fertiliser [52,69]. For example, the study performed by Novak et al [70] showed that the concentration of total P in manure-based biochars was 53 to 105 times higher than that in lignocellulosic-based biochars and the release of dissolved P in soils amended with manurebased biochars was approximately 850 times higher than in the soils amended with lignocellulosic-based biochars.…”
Section: Phosphorusmentioning
confidence: 99%
“…Novak et al [70] examined the release kinetics of K and P from various biochar in fine-loamy soil in a 150-d column leaching experiment, which showed an initial rapid release of dissolved K, followed by a significant decline in the dissolved K content in the leachate from soils supplemented with either poultry litter biochar or 'designer biochar' at a blending ratio of 80:20 pine chip/poultry litter biochar. They also reported that such a blended biochar was aligned with soil P and K levels recommended for corn production in southeastern USA Coastal Plain sandy soils [70].…”
Section: Impact Of Biochar On K Availability In Soilsmentioning
confidence: 99%
“…This is also likely to be the situation for many of the other plant nutrient elements present in biochar. The correspondence between nutrient elements in equivalent biochar and fertilizer rates rests on the assumption that elements in biochar will be released to soil solution within the growth period of crops [26]. The current research has investigated this hypothesis and the mechanisms controlling the release of nutrient elements from biochar.…”
Section: Discussionmentioning
confidence: 99%